2013
DOI: 10.1111/lam.12177
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of protamine with the marine bacterium, Pseudoalteromonas sp. NCIMB 2021

Abstract: Significance and Impact of the Study: Protamine is a cationic antimicrobial peptide (CAP), which is active against a variety of bacteria. This is the first in-depth study of the interaction of protamine with a marine bacterium, Pseudoalteromonas sp. NCIMB 2021. Our results show that protamine is only active in seawater in the absence of divalent cations. In the presence of the divalent cations, Mg 2+ and Ca 2+ , protamine enhances the growth of Pseudoalteromonas sp. NCIMB 2021 and produces chains rather than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The NCIMB 2021 bacteria were grown in ASW:TSB (1:3) prior to inoculation, leading to chains in the inoculum since TSB contains sufficient amino acids to facilitate chain formation. 18 If ASW:TSB (1:3) was also used as the flow-cell medium there were few cells right at the coverslip surface, with long chains extending off the surface. Furthermore, spectra obtained from biofilm in ASW:TSB (1:3) showed a very high background signal, making it an unsuitable medium for flow cell experiments where Raman spectra were to be collected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NCIMB 2021 bacteria were grown in ASW:TSB (1:3) prior to inoculation, leading to chains in the inoculum since TSB contains sufficient amino acids to facilitate chain formation. 18 If ASW:TSB (1:3) was also used as the flow-cell medium there were few cells right at the coverslip surface, with long chains extending off the surface. Furthermore, spectra obtained from biofilm in ASW:TSB (1:3) showed a very high background signal, making it an unsuitable medium for flow cell experiments where Raman spectra were to be collected.…”
Section: Resultsmentioning
confidence: 99%
“…NCIMB 2021 also successfully grew in SSW, in which nitrate was the sole source of nitrogen, and no chains of bacteria were produced unless an amino acid such as glutamate was added. 18 However, SSW was also an unsuitable medium for collection of Raman spectra since it produced two significant peaks at 982 and 1047 cm −1 (attributable to sulfate and nitrate, respectively 19 ). On this basis, ASW, a minimal medium, 4 was chosen, since it did not produce any additional peaks in the Raman region of interest, 1800–700 cm −1 , other than those of water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Pustam and colleagues revealed how the cationic antimicrobial peptide, protamine, enhanced the growth of Pseudoaltermonas sp. in the presence of Mg 2+ and Ca 2+ [ 23 ]. Cationic antimicrobial peptides are associated with killing of Gram-negative bacteria and enhancement of growth would come as a surprise in this regard.…”
Section: Marine Peptides and Cell-cell Communicationmentioning
confidence: 99%
“…Some success has already been achieved through culture independent approaches, using metagenomics to translate the genetic blueprint into active compounds [ 12 , 13 , 14 , 15 ]. In addition, new initiatives are ongoing to improve the culturability of marine isolates, thus enhancing our capacity to produce the novel compounds that are urgently needed [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, perhaps a greater challenge remains the integration of molecular and chemical technologies to maximize our efficiency in this field.…”
Section: Introductionmentioning
confidence: 99%